23 mars : journée de solidarité internationale avec le peuple et les étudiants du Maroc. Liberté pour les prisonniers politiques au Maroc
High contrast, red and black photograph of men behind bars Poster advertising campaign for the release of political prisoners in Morocco PO-1625